THE CIRCULAR ROTUNDA CHURCH IN THE WEST OF PELUSIUM - NORTH SINAI, IN LIGHT OF THE ARCHAEOLOGICAL EXCAVATIONS - Sayed Mohamed Al Hadi (International Journal of Cultural Inheritance & Social Sciences ISSN: 2632-7597, 2019)
In this paper I will discuss the study of the circular church west of Pelusium. It has a unique style in the architecture of churches, especially in Egypt. This circular church is considered the only discovered in Egypt and there is no church like it inside Egypt, and I will mention the role of Sinai in the transmission of Christianity through it to Egypt from Palestine, the spread of monasticism and the most important Christian places in both south and north Sinai, as well as it was linked to the flight of the Holy family to Egypt especially Pelusium city. And I will talk about the most important Saints of Pelusium, the main planning of the churches and their important styles. Then I explained the circular church in the light of the excavations, their location, their history, their baptistery and their architectural description especially the eastern (Rotunda) and western building (crypt). The research ended with result proving that the western building (the crypt) was more recentthan the eastern building (Rotunda).